Novos protótipos de dois dessalinizadores térmicos para operação no fogão solar com aquecimento indireto - Costa, Isaias Silva da (2013)
This work presents two new prototypes of a circular desalinator operation in a solar cooker for indirect heating. The first prototype, called Type A, produces desalinated water from brackish water deposited in the pan solar cooker. In the second prototype, the Type B, the brackish water pan is used only as a means of transfering heat to the first tray tower desalination. These prototypes were fabricated and tested in LESGN (Solar Energy Laboratory and Natural Gas). Its structure consists of stainless steel plates, trays with circular and inclined downwards (with circular trays to facilitate the flow of condensed water) and "pipes" (that harvest desalinated water and take out the stages and side rails, harvesting the water that condenses the side walls). The desalting tower was formed by a set of trays to facilitate the handling and operation. The experiments were conducted between 7.00am and 5.00pm and the maximum number of stages was three. Experiments with 2 and 3 stages confirmed the heat recovery process, in other words, the repeated use of the heat stored in the desalinated water in a lower stage by stage above. The experimental results showed that the maximum production were daily for the Type A, 4.72 L with 3 stages, and the desalinator Type B 3.50 L also with 3 stages. It was found that the efficiency of desalination type A was greater than that of Type B, which explains why Type B has a further resistance to heat transfer. On the other hand, Type B prototype allows continued operation of the desalination tower, not requiring the dismantling after each emptying process of the water in the pan